Acquiring control: The evolution of ROS-Induced oxidative stress and redox signaling pathways in plant stress responses - Farooq, Muhammad Ansar; Niazi, Adnan Khan; Akhtar, Javaid; Saifullah; Farooq, Muhammad; Souri, Zahra; Karimi, Naser; Rengel, Zed (Plant physiology and biochemistry, 2019)
Reactive oxygen species (ROS) – the byproducts of aerobic metabolism – influence numerous aspects of the plant life cycle and environmental response mechanisms. In plants, ROS act like a double-edged sword; they play multiple beneficial roles at low concentrations, whereas at high concentrations ROS and related redox-active compounds cause cellular damage through oxidative stress. To examine the dual role of ROS as harmful oxidants and/or crucial cellular signals, this review elaborates that (i) how plants sense and respond to ROS in various subcellular organelles and (ii) the dynamics of subsequent ROS-induced signaling processes. The recent understanding of crosstalk between various cellular compartments in mediating their redox state spatially and temporally is discussed. Emphasis on the beneficial effects of ROS in maintaining cellular energy homeostasis, regulating diverse cellular functions, and activating acclimation responses in plants exposed to abiotic and biotic stresses are described. The comprehensive view of cellular ROS dynamics covering the breadth and versatility of ROS will contribute to understanding the complexity of apparently contradictory ROS roles in plant physiological responses in less than optimum environments. •The evolution of ROS as harmful oxidants and/or universal signaling metabolites in eukaryotic cells is critically appraised.•A comprehensive view of cellular ROS dynamics, with particular emphasis on crosstalk between cellular compartments in mediating their redox state spatially and temporally is discussed.•The beneficial roles of ROS to regulate a diverse array of plant cellular responses under stress conditions are highlighted.